2018
DOI: 10.1002/jor.23813
|View full text |Cite
|
Sign up to set email alerts
|

The onset of fretting at the head‐stem connection in hip arthroplasty is affected by head material and trunnion design under simulated corrosion conditions

Abstract: Mechanically assisted crevice corrosion (MACC) is a mechanism for trunnion damage in total hip arthroplasties (THAs). Retrieval studies have shown reduced MACC-related damage for ceramic heads compared with cobalt-chromium (CoCr) heads. We propose that ceramic heads demonstrate fretting at higher cyclic compressive loads than CoCr heads on titanium alloy trunnions in a simulated corrosion model. A closed electrochemical chamber was used to measure fretting current onset loads for two modern titanium alloy trun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The results of the electrochemical fretting corrosion test are important for understanding the effect of design changes, load application modes, and combination of components made from different materials. Recently, use of electrochemical tests by Rowan et al [4] evaluated the effect of two different designs (V40 and 12/14) of titanium alloy taper and two different head materials (Co-Cr and ceramic) on the fretting corrosion. They showed that the V40 taper with ceramic head presented the lowest propensity to fretting corrosion than the same taper with a Co-Cr head.…”
Section: Materials and The Methods Of Electrochemical Testingmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the electrochemical fretting corrosion test are important for understanding the effect of design changes, load application modes, and combination of components made from different materials. Recently, use of electrochemical tests by Rowan et al [4] evaluated the effect of two different designs (V40 and 12/14) of titanium alloy taper and two different head materials (Co-Cr and ceramic) on the fretting corrosion. They showed that the V40 taper with ceramic head presented the lowest propensity to fretting corrosion than the same taper with a Co-Cr head.…”
Section: Materials and The Methods Of Electrochemical Testingmentioning
confidence: 99%
“…The modular type of hip prosthesis has become widely used, because it provides a better fit to the patient's anatomy, since it is possible to combine components of different sizes, types and materials [2], [3]. Surgeons may also perform femoral head replacement on already fixed stems, for a less aggressive revision procedure [4], [5]. The head-stem modular connection of the hip prosthesis usually consists of a metal-on-metal conical junction where the femoral stem has a conical tip and the femoral head has the tapered bore for fitting, as can be seen in Fig 1. Hip prostheses may vary from manufacturer to manufacturer, in terms of angle of the taper and bore of the head (one example can be seen in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations